Saturday Night Peter - Kay, Peter (London Century, 2009)
This is the long-awaited follow up to "The Sound of Laughter". Picking up from where Peter's massive bestselling autobiography "The Sound of Laughter" left off, "Saturday Night Peter" charts the hilarious journey his career took as he developed and honed his comedy skills by taking to the road and trying out his stand up material in pubs and clubs across the country. Each Saturday night would present Peter with a new venue, a new audience to win over, other acts appearing and the ever changing and all important performance itself. But behind the scenes there were the digs and landladies, the preparation for the show, the anxious drive there and of course the inspiration for the material itself.
Include Color Illustrations
Keywords: Television Actors and Actresses -- Comedians -- Great Britain -- Biography